ANTIOXIDANT AND ANTIBACTERIAL IN VITRO ACTIVITY OF THE GLYCOLIC EXTRACT FROM THE FLOWERS OF Senna birostris “MUTUY” AND ITS POTENTIAL COSMETIC APPLICATIONS - del Carpio Jimenez, Carla (2025)
The cosmetic industry is undergoing a transformation driven by a deeper understanding of skin health and scientific advancements. This has led to the development of dermocosmetics, a unique category between cosmetics and pharmaceuticals. One prominent trend in this field is the identification of active compounds from plant sources. For example, four important bioactive polyphenols found in Senna species—astragalin, kaempferol, rhein, and aloe-emodin—show potential for treating atopic dermatitis. In some communities in Cusco, a shrub with bright yellow flowers called Senna birostris is grown. The crushed leaves of this plant are traditionally used to heal wounds, while in other countries, it is employed in the treatment of herpes and various other skin conditions. The objective of this research was to determine the antioxidant and antibacterial activity against Staphylococcus aureus of the glycolic extract of Senna birostris flowers and its possible dermo-cosmetic application. The antioxidant activity was determined using the DPPH free radical inhibition method establishing the percentage inhibition and the mean inhibitory concentration (IC50) and the antibacterial activity was established through the dug well method. The percentage inhibition of DPPH at a concentration of 100μg/mL was 71.0%, with an IC50 of 66.33 ± 1.753 μg/mL. Regarding the antibacterial activity, an inhibition zone of 9.00 ± 0.32 mm could be obtained at the concentration of 100%. The glycolic extract of S. birostris flowers demonstrated its free radical inhibition activity and antibacterial activity, which would support its dermo-cosmetic use.